Modelling the silicate emission features in type 1 AGNs: Dusty torus and disk+outflow models. Issue Volume 15:Issue S359(2020) (March 2019) - Martínez-Paredes, M.; Aretxaga, I.
Abstract: We investigated how the most common dusty torus models reproduce both the 10 and 18μm silicate emission features observed in the nuclear infrared (IR) Spitzer spectrum of type 1 active galactic nuclei (AGN). We use a sample of type 1 AGN for which the Spitzer spectrum is mostly dominated by the emission of the AGN (>80%), and the 10μm silicate emission feature is prominent (1σ Si 10 μm > 0.28). The models are the smooth dusty torus models from Fritz et al., the clumpy dusty torus models from Nenkova et al. and Hoenig et al., the two-phase media torus model from Stalevski et al., and the disk+outflow model from Hoenig et al. These models differ by assuming either different geometry or dust composition. We found that in general, all models have difficulties reproducing the shape and peak of the silicate emission features, but the disk+outflow model is the best reproducing the AGN-dominated Spitzer spectrum.